BODY SHAMING DI SEKOLAH SEBAGAI BENTUK VIKTIMISASI TERHADAP PEREMPUAN (Studi Kasus Kepada Siswi Korban Body Shaming di SMAN X Pekanbaru) - Askarial; Nisa Nurjanah, Maya (UIR PRESS, 2021)
Body shaming is generally in the form of verbal utterances that can lead to bullying and can lead to verbal abuse. Where this body shaming problem often occurs and without us knowing it. This body shaming behavior is still underestimated and is considered culturally normal. The purpose of this study was to discuss how the form of victimization experienced by obese adolescent girls as victims of body shaming at SMAN X Pekanbaru. This research uses qualitative methods and type of case study research. The main theory in this study uses the feminist theory of intersectionality in feminist criminology studies and the concept of self-objectification in the theory of objectification. This theory explains that the existence of a self-identity inherent in the victim results in body shaming resulting in victimization. From this problem, the researcher sees several aspects as a form to minimize the occurrence of body shaming so that it does not develop among students, the role of several parties is needed, namely the Pekanbaru City Education Office, the school, the student council, and parents participate in dealing with this problem.